The Effect of Consumption of JAKATE Cokkies (Corn, Green Beans, Tempeh) on the Nutritional Status of Toddlers - Rosalinna, Rosalinna; Paryono, Paryono; Kurniarum, Ari (Poltekkes Kemenkes Palembang, 2025)
In Indonesia, the problem of nutrition in toddlers is still a public health problem, especially in areas with low levels of nutrition. The purpose of this study was to see how Cokkies JAKATE (corn, green beans, and tempeh) given as additional food affects the health of toddlers aged 24 to 59 months who are malnourished. In Ngrundul Village, Kebonarum District, Klaten Regency, there were 50 toddlers involved in this study, which was conducted using a quantitative approach with a single-group pretest-posttest design. Data were collected through anthropometric measurements before and after the intervention, and the Wilcoxon statistical test was used to analyze it. The results showed that after the 14-day intervention, the toddlers' weight increased by an average of 0.49 kg and the average height by 1.22 cm, with a p value of 0.05 each. This shows that the provision of Cokkies JAKATE has a significant impact on improving toddler nutrition. Foods such as green beans, corn, and tempeh contain vegetable protein, vitamins, and minerals that can help growth and increase weight quickly. This study shows that the use of local supplementary food can be an effective method to prevent malnutrition in children. To ensure that similar programs are successful at the community level, long-term implementation and sustainability monitoring are essential.